Best friends and drama queens - Cabot, Meg (New York Scholastic Press, 2009)
Nine-year-old Allie Finkle's list of rules helps her navigate a tricky situation with a new girl at school
Hurg
5 8
Keywords: Behavior -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Schools -- Fiction